Social psychology at work essays in honour of Michael Argyle - Collett, Peter (Routledge, 1995)
Social Psychology at Work is a rich source book of up-to-date ideas, research findings and reviews at the interface of pure and applied psychology. It will be important and rewarding reading for all those such as students, consultants and managers and trainers who are interested in psychology at work
Keywords: Arbeids- en organisatiepsychologie; Sociale psychologie; Psychology, Industrial; Arbeitspsychologie; Industriepsychologie; Betriebspsychologie; Aufsatzsammlung; Festschrift